Universal chromosomal microarray analysis reveals high proportion of copy‐number variants in low‐risk pregnancies. (5th April 2021) - Stern, S.; Hacohen, N.; Meiner, V.; Yagel, S.; Zenvirt, S.; Shkedi‐Rafid, S.; Macarov, M.; Valsky, D. V.; Porat, S.; Yanai, N.; Frumkin, A.; Daum, H.
ABSTRACT: Objectives: To evaluate the yield and utility of the routine use of chromosomal microarray analysis (CMA) for prenatal genetic diagnosis in a large cohort of pregnancies with normal ultrasound (US) at the time of genetic testing, compared with pregnancies with abnormal US findings. Methods: We reviewed all prenatal CMA results in our center between November 2013 and December 2018. The prevalence of different CMA results in pregnancies with normal US at the time of genetic testing ('low‐risk pregnancies'), was compared with that in pregnancies with abnormal US findings ('high‐risk pregnancies'). Medical records were searched in order to evaluate subsequent US follow‐up and the outcome of pregnancies with a clinically relevant copy‐number variant (CNV), i.e. a pathogenic or likely pathogenic CNV or a susceptibility locus for disease with > 10% penetrance, related to early‐onset disease in the low‐risk group. Results: In a cohort of 6431 low‐risk pregnancies that underwent CMA, the prevalence of a clinically significant CNV related to early‐onset disease was 1.1% (72/6431), which was significantly lower than the prevalence in high‐risk pregnancies (4.9% (65/1326)). Of the low‐risk pregnancies, 0.4% (27/6431) had a pathogenic or likely pathogenic CNV, and another 0.7% (45/6431) had a susceptibility locus with more than 10% penetrance. Follow‐up of the low‐risk pregnancies with a clinically significant early‐onset CNV revealed that 31.9% (23/72) were terminated, while outcome data were missing in 26.4% (19/72). In 16.7% (12/72) of low‐risk pregnancies, an US abnormality was discovered later on in gestation, after genetic testing had been performed. Conclusion: Although the background risk of identifying a clinically significant early‐onset abnormal CMA result in pregnancies with a low a‐priori risk is lower than that observed in high‐risk pregnancies, the risk is substantial and should be conveyed to all pregnant women. © 2020 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Baert et al. Click here to view the Correspondence.